Influencia del alimento extruido en el crecimiento de alevinos de paiche (Arapaima gigas) utilizando diferentes tasas de alimentación, bajo sistema de cultivo en Jaulas Flotantes - García Córdova, Carlos Fernando (2010)
This study entitled “Influence of sowing density on growth of fries of paiches reared in floating cages” lasted 146 days which the way was evaluated of how food affects the growth of this specie; we worked under a principal of three treatments with three repetitions for each treatment and a witness group of comparison. The results indicate that existed significant difference; being the treatment with 8% rate of nourishment which have presented better conditions, with a feed conversion index of 4, 5 and a daily growth index of 14g/day, in relation to other treatment that have presented the results below this, which demonstrates that at a rate below 8% is not sufficient for normal development of this specie, concluding of that if the extruded food affects the growth of fries of paiches reared in floating cages.